Health management in backyard poultry under field conditions - Kolluri, Gautham; Kumar, Asok; Yadav, M Ajit Singh; Palanivelu, M (Indian Farming, 2020)
Of several infections, Newcastle disease and Avian influenza poses a potential health risk for the backyard poultry and was the major cause for mortalities. In village chicken production, it is single greatest constraint limiting its productivity and development throughout the developing sphere. Several outbreaks of avian influenza were reported in backyard poultry in the country that result in massive culling of birds in villages. Periodical vaccination once in 6 months with thermostable vaccines against ND may help reducing the infectious pressure. Indigenous traditional knowledge using locally available herbs are the most commonly used for treatment of common ailments in village production system. However, practicing of village biosecurity by the farmers is important for the prosperity of rural/backyard poultry production. It is also important to protect the birds from predation which is a commonly reported loss in backyard system.